PROFITABILITY, INVESTMENT DECISIONS, FUNDING DECISIONS, AND ITS EFFECT ON COMPANY VALUE - Abidah Dwi Rahmi Satiti; Eli Luthfianah (Sean Institute, 2022)
This study aims to determine the effect of profitability, investment decisions and funding decisions on firm value. This research is a quantitative research . The population of this study consists of 12 pharmaceutical sector companies listed on the Indonesia Stock Exchange. The sample consists of 9 companies with an observation period of 6 years, with a total of 50 samples. The data analysis method used is descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that profitability has an effect on firm value, funding decisions have an effect on firm value, and investment decisions have no effect on firm value.